Association of meteorological factors with the frequency of primary rhegmatogenous retinal detachment in Japan - Masanobu Iida (Nature Portfolio, 2021)
Abstract This 5-year ecological study assessed the association between meteorological factors and rhegmatogenous retinal detachment (RRD) frequency in 571 eyes of 543 cases of primary RRD at the Jikei University Kashiwa Hospital, Japan. We examined the monthly and seasonal distributions of RRD frequency using one-way analysis of variance. We then evaluated the relationship between monthly RRD frequency and 36 meteorological parameters using Poisson regression analysis. Furthermore, we developed multivariate regression models to predict the frequency of RRD based on specific meteorological parameters. There were no significant differences in the monthly and seasonal distributions (monthly, P = 0.99; seasonal, P = 0.77). The following eight parameters were associated with a lower RRD frequency: average sea level barometric pressure and average daily variation of average temperature, maximum temperature, maximum wind speed, maximum instantaneous wind speed, humidity, average sea level barometric pressure, and minimum sea level barometric pressure (P < 0.05). The best model to predict RRD frequency showed sufficient validity (Akaike’s information criterion with correction for small sample size = 332.0) and predictive power (proportion of variance explained by cross-validation method = 84.82%, 95% CI 72.18–93.72). In conclusion, low atmospheric pressure and high meteorological stability are significantly associated with a higher frequency of RRD. In addition, the Poisson regression analysis showed sufficient validity and predictability for predicting RRD frequency.